Book Reviews - Tate, Roger D.; Pennington, Loren E.; Gentry, Robert J.; Pease, Arthur S.; Spidle, Jake W.; Shea, William L.; Tate, Michael L.; Sellen, Robert W.; Coate, Charles; Nickell, Frank; Marran, James F.; Diem, Richard A.; et al. (Teaching History: A Journal of Methods, 1983)
H. Wayne Morgan. Drugs in America: A Social History, 1800-1980. Syracuse, New York: Syracuse University Press, 1981. Pp. xi, 233. Cloth, $20.00. Review by Roger D. Tate of Somerset Community College. Michael T. Isenberg. War on Film: The American Cinema and World War I, 1914-1941. Rutherford, New Jersey: Fairleigh Dickinson University Press, 1981. Pp. 273. Cloth, $27.50. Review by Loren E. Pennington of Emporia State University. Bertell Ollman and Edward Vernoff, eds. The Left Academy: Marxist Scholarship on American Campuses. New York: McGraw-Hill Book Co., 1982. Pp. vii, 290. Paper, $8.95. Review by Robert J. Gentry of The University of Southwestern Louisiana. James West Davidson and Mark Hamilton Lytle, eds. After the Fact: The Art of Historical Detection. New York: Alfred A. Knopf, 1982. Vol. I: Pp. xxxii, 204. Paper, $6.95. Vol. II: Pp. xxxii, 220. Paper, $6.95. Review by Arthur S. Pease of Lebanon School District, Lebanon, N.H. David Birmingham. Central Africa to 1870: Zambezia, Zaire and the South Atlantic. New York: Cambridge University Press, 1981. Pp. vii, 177. Paper, $9.95. Review by Jake W. Spidle of the University of New Mexico. James Kirby Martin and Mark Edward Lender. A Respectable Army: The Military Origins of the Republic, 1763-1789. Arlington Heights, Illinois: Harlan Davidson, Inc., 1982. Pp. xvi, 240. Paper, $7.95. Review by William L. Shea of the University of Arkansas at Monticello. Bruce A. Rosenberg. The Code of the West. Bloomington: Indiana University Press, 1982. Pp. vi, 213. Cloth, $15.00. Review by Michael L. Tate of the University of Nebraska at Omaha. Ralph B. Levering. The Cold War, 1945-1972. Arlington Heights, Illinois: Harlan Davidson, Inc., 1982. Pp. xi, 165. Paper, $6.95. Review by Robert W. Sellen of Georgia State University. Fay D. Metcalf and Matthew T. Downey. Using Local History in the Classroom. Nashville: American Association for State and Local History, 1982. Pp. x, 284. Cloth, $17.50. Review by Charles Coate of Eastern Oregon State College. William Graebner and Leonard Richards, eds. The American Record: Images of the Nation's Past. New York: Alfred A. Knopf, 1982. Vol. I, Pp. 421. Paper, $9.95. Vol. II, Pp. 449. Paper, $9.95. Review by Frank Nickell of Southeast Missouri State University. Thomas Ladenburg and Christopher Bairstow. Who Killed JFK: Need We Know? Brookline, Massachusetts: Brookline-Cambridge Dissemination Center, 1978. Pp. 31. Paper, $1.10. Review by James F. Marran of New Trier Township High School, Winnetka/ Northfield, Illinois. Thomas Ladenburg. America in Indochina. Brookline, Massachusetts: Brookline-Cambridge Dissemination Center, 1977. Pp. 50. Paper, $1.40. Review by Richard A. Diem of The University of Texas at San Antonio. Thomas J. Schlereth. Artifacts and the American Past. Nashville, Tennessee: American Association for State and Local History, 1980. Pp. vii, 294. Cloth, $13.95. Review by Michael B. Husband of Palisade, Colorado.